Simultaneous quantification of 19 nonsteroidal anti‐inflammatory drugs in oral fluid by liquid chromatography‐high resolution mass spectrometry: Application on ultratrail runner's oral fluid. Issue 4 (19th January 2022) - Mashal, Mohammad Shafiq; Nalin, Marie; Bevalot, Fabien; Sallet, Pierre; Guitton, Jérôme; Machon, Christelle
Abstract: Nonsteroidal anti‐inflammatory drugs (NSAIDs) are a therapeutic class suspected to be used by ultratrail runners. The use of NSAIDs during ultratrails is known to be associated with various adverse effects. To study the prevalence of NSAIDs intake in ultratrail runners, oral fluid (OF) is a relevant matrix as it is noninvasive and easy to collect. The aim of our work was to develop and validate a liquid–liquid extraction followed by a liquid chromatography (LC)–mass spectrometry (MS)/high resolution mass spectrometry (HRMS) method for the simultaneous quantification of 19 NSAIDs in OF. After a comparison of different liquid–liquid extraction methods, a double step liquid–liquid extraction with chloroform was performed on OF collected with Quantisal®, with extraction recoveries higher than 90%. An Accucore AQ column was selected for the chromatographic separation of NSAIDs. The Q Exactive Plus mass spectrometer operated in full scan and ddms2 mode after positive and negative electrospray ionization. Selectivity, carry‐over, matrix effect, and linearity were validated for all NSAIDs. Within‐day and between‐day accuracy and precision were validated for all NSAIDs (<15% for quality control [QC] samples and <20% for lower limit of quantitation [LLOQ]), except within‐day accuracy for the LLOQ of mefenamic acid. A stability study was also performed on OF at room temperature and +4°C. The method was applied on OF from runners who participate to Ultra Trail du Mont Blanc®. Abstract : Nonsteroidal anti‐inflammatory drugs (NSAIDs) are a therapeutic class suspected to be widely used by ultratrail runners. It is of interest to be able to search NSAIDs in ultratrail runners because of their adverse effects, the ignorance of these effects by ultratrail runners, the misusage of NSAIDs, and to contribute to a clean sport.